Village Funds: A Study of an Implementation Poverty Alleviation Program in Indonesia - Nuraini, Siti; Ardianti, Riski Isminar; Eka Sari, Jayanti Dian (International Journal of Psychosocial Rehabilitation, 2020)
Poverty-alleviation policies seek to increase regional economic productivity thereby contributing to national income for developing countries. As one of the national programs expected to reduce poverty, village funds are expected to directly touch the problem of poverty in rural areas. Based on the needs of each village, this program focuses on the priority of use and benefits that can be received directly by the community. This research will examine the implementation of village funds from 2015 until now in East Java as part of the poverty-alleviation programs. The research used qualitative description, including in-depth interviews, observations and a literature review. As such programs are expected to reduce poverty, the majority of village funds in East Java are dominated by infrastructure with a labor-intensive approach for the poor, so they only have a short-term effect on the process of poverty reduction. Besides the success of the program, it turned out that there was some misuse by persons on the village level.